Biofilm Formation of Candida albicans Facilitates Fungal Infiltration and Persister Cell Formation in Vaginal Candidiasis - Wu, Xueqing; Zhang, Sisi; Li, Haiying; Shen, Laien; Dong, Chenle; Sun, Yao; Chen, Huale; Xu, Boyun; Zhuang, Wenyi; Deighton, Margaret; Qu, Yue (Frontiers in Microbiology, 2020)
Background: Vaginal candidiasis is an important medical condition awaiting more effective treatment. How Candida albicans causes this disease and survives antifungal treatment is not yet fully understood. This study aimed to establish a comprehensive understanding of biofilm-related defensive strategies that C. albicans uses to establish vaginal candidiasis and to survive antifungal treatment. Methods: A mouse model of vaginal candidiasis was adopted to examine the formation of biotic biofilms on the vaginal epithelium and fungal infiltration by laboratory and clinical strains of C. albicans. Histopathological changes and local inflammation in the vaginal epithelium caused by C. albicans of different biofilm phenotypes were compared. Antifungal susceptibility testing was carried out for C. albicans grown as planktonic cells, microplate-based abiotic biofilms, and epithelium-based biotic biofilms. Formation of persister cells by C. albicans in different growth modes was also quantified and compared. Results: C. albicans wild-type reference strains and clinical isolates, but not the biofilm-defective mutants, formed a significant number of biotic biofilms on the vaginal epithelium of mice and infiltrated the epithelium. Biofilm formation and epithelial invasion induced local inflammatory responses and histopathological changes in the vaginal epithelium including neutrophil infiltration and subcorneal microabscesses. Biofilm growth on the vaginal epithelium also led to high resistance to antifungal treatments and promoted the formation of antifungal-tolerant persister cells. Conclusions: This study comprehensively assessed biofilm-related microbial strategies that C. albicans uses in vaginal candidiasis, and provided experimental evidence to support the important role of biofilm formation in the histopathogenesis of vaginal candidiasis and the recalcitrance of the infection to antifungal treatment.